Development of modeling theоretical studies on fractionating distillation parameters of natural sources of aroma - Frolova, Natalia; Yushchenko (Gonchar), Natalia (My University, 2018)
Ir this paper the results of theoretical justification of coherence of scuing model regimes of distillation of essential oils into separate aroma fractions, w hich arc highly concentrated flavors of long-term storage, arc represented. High-performance essential oils distillation requires adherence to strict ptocess condition», cnicial for regulating fraction's aroma. Complexity in determining of such regimes consist in duration of experimental cistillations with mentioned essential oils expenses.Theoretical modelling of distillation parameters provides, though real deflations. development of set fraction’s aroma on account of collecting key aromatic components and a number of others, similar to the ley ones in ftgitivcncss and boiling point, into a separate fraction.To nxtdcl regimes of essential oil fraction distillation valid Tboil of essential oils components at ambient pressure, equilibrium picssurcs of essential oils distillation, value of relative faptiveness of a. as ratio of ptcssurcs at a constant temperature, are attributed A mint nun number of theoretically perfect plates and operating reflux ratio were taken into account.Fraction distillation doesn’t ruin natural structural bond of essential oils compounds, preserves their biologic ability. Combining fractions of one essential oil or various ones by the determined moss ratios provides nunerous variants of natural flavors for usage in food, in parti.-ular dairy industry.
Keywords: аромат; aroma; моделювання; modeling; фракційної перегонки; fractionating distillation; кафедра технології ресторанної і аюрведичної продукції; кафедра технології молока і молочних продуктів